(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The world is creatively developing, it additionally acquires the fame of buying motivation. Many variables, qualities and specifications impact buying motivation. This study plans to explore the explanation and motivational factors that make HPL Influencers energetic and excited with regard to purchase decisions while buying HPL. A customer is driven by family, culture,sub-culture,friends,colleagues,society,advertisements,packaging, etc. Several other factors were examined like price, brand ,etc. This study will help to understand all the factors that are influencing the influencers. This study focuses on different motivational factors to the influencers for the selection of High Pressure Laminates(HPL). This study reveals that low price of HPL, catalogue presentation of HPL,credit period given by theretailers are the most preferred factors and different thickness in same design of HPL, Test certificates of the HPL are the lease preferred factors.